Shear-wave manipulation by embedded soft devices. (February 2021) - Chen, Linli; Ma, Chao; Zhao, Shiheng; Zheng, Pingping; Zhao, Qian; Chang, Zheng
Abstract: In accordance with hyperelastic transformation theory, a range of shear-wave manipulation devices can be designed with neo-Hookean materials pre-deformed properly. However, how such devices fit the background medium remains elusive. In this study, a systematic formula is developed in terms of elastic wave transmission and reflection between un-deformed and pre-deformed hyperelastic materials. By both theoretical analyses and numerical simulations, the shear-wave propagation from an un-deformed neo-Hookean material to the pre-deformed one is investigated. Among the three typical deformations, "constrained" uniaxial tension and simple-shear are found to be able to ensure total transmission, whereas ordinary uniaxial tension and hydrostatic compression could cause reflection. Thus, three embedded shear-wave manipulation devices are proposed, namely, a unidirectional cloak, a splicing beam bend and a concave lens; their performance is verified by numerical simulations. This study may underpin the design and realization of soft-matter-based wave control devices. Potential applications can be expected in nondestructive testing, impact protection, biomedical imaging, as well as soft robotics.